2014
DOI: 10.4103/1596-3519.142293
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of hepatitis B and C among mentally ill patients attending a tertiary hospital in Nigeria

Abstract: Mentally ill patients attending UITH were significantly infected with hepatitis C virus. There is need for interventional measures to reduce the prevalence of hepatitis C among the mentally ill population such as health education and early screening of mentally ill in our setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…In a study performed by Dinwiddie et al with 1556 psychiatric patients, HBSAg positivity was 27.8% [17]. However, in a more recent study with 350 psychiatric patients, HBSAg positivity was 10% [18]. Several studies have been performed in Turkey showed that seropositivity decreased from 11.8% [15] to 2.7% within years in the hospitalized psychiatric patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a study performed by Dinwiddie et al with 1556 psychiatric patients, HBSAg positivity was 27.8% [17]. However, in a more recent study with 350 psychiatric patients, HBSAg positivity was 10% [18]. Several studies have been performed in Turkey showed that seropositivity decreased from 11.8% [15] to 2.7% within years in the hospitalized psychiatric patients [16].…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 To our knowledge data on HBV occurrence among these patients are limited, and data on the literature have focused on prevalence of HBV infection. 14 , 15 , 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%